Identification of apolipoprotein B–reactive CDR3 motifs allows tracking of atherosclerosis-related memory CD4+T cells in multiple donors - Roy, Payel; Suthahar, Sujit Silas Armstrong; Makings, Jeffrey; Ley, Klaus (Frontiers in Immunology, 2024)
Atherosclerosis is a major pathological condition that underlies many cardiovascular diseases (CVD). Its etiology involves breech of tolerance to self, leading to clonal expansion of autoreactive apolipoprotein B (APOB)-reactive CD4 + T cells that correlates with clinical CVD.The T cell receptor (TCR) sequences that mediate activation of APOB-specific CD4 + T cells are unknown. In a previous study, we had profiled the hypervariable complementarity determining region 3 (CDR3) of CD4 + T cells that respond to six immunodominant APOB epitopes in most donors. Here, we comprehensively analyze this dataset of 149,065 APOB-reactive and 199,211 non-reactive control CDR3s from 6 HLA-typed donors and identified 672 highly expanded (frequency threshold>1.39E-03) clones that were significantly enriched in the APOB-reactive group as compared to the controls (log10 odds ratio≥1, Fisher's test p<0.01). Analysis of 114,755 naïve, 91,001 central memory (TCM) and 29,839 effector memory (TEM) CDR3 sequences from the same donors revealed that APOB+ clones can be traced to complex repertoire of unenriched blood T cells. The fraction of APOB+ clones that overlapped with memory CDR3s ranged from 2.2 to 46% (average 16.4%). This was significantly higher than their overlap with the naïve pool, which ranged from 0.7 to 2% (average 1.36%). CDR3 motif analysis with the machine learning-based in silico tool, GLIPH (grouping of lymphocyte interactions by paratope hotspots), identified 532 APOB+ motifs. Analysis of naïve and memory CDR3 sequences with GLIPH revealed that ~40% (209 of 532) of these APOB+ motifs were enriched in the memory pool. Network analysis with Cytoscape revealed extensive sharing of the memory-affiliated APOB+ motifs across multiple donors. We identified 6 motifs that were present in TCM and TEM CDR3 sequences from >80% of the donors and were highly enriched in the APOB-reactive TCR repertoire. The identified APOB-reactive expanded CD4 + T cell clones and conserved motifs can be used to annotate and track human atherosclerosis-related autoreactive CD4 + T cells and measure their clonal expansion.